Plan Parcial De Renovación Urbana Kf93 (Kennedy Ferrea 93) - Naranjo Bonilla, Cristian Leonardo (Universidad Antonio Nariño, 2022)
The partial urban renovation plan KF93 (Kennedy Férrea 93), is focused on the strategic improvement of the most important factors within the UPZ'S Timiza and Carvajal, of them, the most important within the study area are the public space and green areas which are in invasion or deterioration, as well as the economic sector of this zone, such as the workshops on the old lane (Transversal 72d), without leaving aside the history of the place as well as the culture of its inhabitants.